A Review of the Clinical Aspects of Transmissible Venereal Tumour in Dogs - Olfat, Ghulam Haidar (Journal of Natural Sciences – Kabul University, 2020)
Transmissible Venereal Tumours (TVTs) are a common neoplasm in dogs, typically observed in those in close contact with each other or in stray and wild dogs grouped together in exhibitions. Transmission occurs through sexual intercourse and via direct contact with the mucous membranes of both male and female dogs, resulting in numerous neoplastic masses in the external genitalia. Damaged mucous membranes can facilitate transmission. Most young dogs (under five years old) are infected. The tumour grows rapidly, and clinical symptoms appear shortly after the incubation period. It is characterized by malodorous and bloody secretions. Upon removal of the nodular bodily mass from the penis, a grayish color is observed. The history, symptoms, and clinical cytological features are usually sufficient for diagnosis; however, biopsy and oncological examination may be necessary in unusual cases.